Analysis of percutaneous kyphoplasty under different types of anesthesia for the treatment of multiple osteoporotic vertebral fractures - Shuai Zhang (BMC Musculoskeletal Disorders, 2020)
Abstract Background Surgeons recognize that using percutaneous kyphoplasty (PKP) under local anesthesia to treat osteoporotic vertebral fracture (OVF) prevents interference with the general situation of elderly patients suffering from multiple organ dysfunction. Surgeons can directly assess whether nerve injury occurs while the patient is awake. However, when patients with multiple osteoporotic vertebral fractures (m-OVFs) receive local anesthesia, fluoroscopy time often has to be increased, the operative time has to be extended, or the operation has to be terminated because of discomfort related to body posture. No relevant study has thus far been conducted on the type of anesthesia to administer to patients undergoing PKP for m-OVFs. This study aimed to determine which of the two types of anesthesia is more suitable for PKP for m-OVFs. Methods A retrospective study was conducted involving 159 patients who underwent PKP for m-OVFs from January 2016 to January 2020; 81 patients underwent PKP under general anesthesia (Group G), and 78 patients underwent PKP under local anesthesia (Group L). Clinical and adverse events were compared between the two groups. Results The intraoperative mean arterial pressure, average heart rate, average fluoroscopy times of each vertebral body, and operative time were less in Group G than in Group L. The visual analog scale (VAS) score was significantly lower after than before the operation. The anterior vertebral height (AVH), middle vertebral height (MVH), and kyphotic angle (KA) were significantly improved in both groups postoperatively. The improvement in VAS score, AVH, MVH, and KA in Group G were higher than those in Group L. No significant difference in the incidence of complications was observed between the two groups. Conclusion PKP under either general anesthesia or local anesthesia was reliable. Compared with PKP under local anesthesia, PKP under general anesthesia could more reliably maintain the stability of vital signs, alleviate preoperative pain in patients, and attain a better orthopedic effect. Moreover, the latter does not increase the complications of patients with m-OVFs. However, the high medical expense of PKP under general anesthesia is a factor to consider when choosing the type of anesthesia.